OPERATIONS OF INTERNATIONAL CRISIS MANAGEMENT AS A PART OF SECURITY AND DEFENSE POLICY OF THE REPUBLIC OF BULGARIA - PETROVA, Elitsa Stoyanova; NICHEV, Nikolay (Annals of Spiru Haret University. Economic Series, 2016)
Abstract The current scientific publication follows the invitation of scientists from the University of Defense in the Czech Republic, Brno for joint international study on economic diplomacy and peacekeeping. The paper presents the role of the Bulgarian army in the operations of international crisis management as part of the security and defense policy of the country, and characteristics of the activities of armed forces in international operations for crisis management. The article focuses on national contribution to international efforts in support of peace and stability, the legal basis for the participation of the Armed Forces of the Republic of Bulgaria in allied and coalition operations and support operations and military participation of the Republic of Bulgaria in international missions and operations.